Cost-it-right (cir) as learning innovative tool in management accounting - Mustafa, Lily Mazlifa; Wan Abdul Rahman, Nor Hawani; Mat Bahari, Anis Barieyah; Jamaluddin, Sabariah; M. Yacob, Noor Hasimah; Mohammad Fadzillah, Nur Syazwani (GADING Journal for the Social Sciences, 2023)
This paper aims to share the viewpoint of the authors on the understanding and importance of using innovative tool in teaching and learning management accounting subject. Rapid changes in technologies require educators to blend innovative advancement as a new way of teaching method with conventional approach. This study was conducted by analysing findings from previous studies and associated with the facts that occur at this time. It provides evidence that the creation of the Cost-It-Right (CIR) system offers users with hands-on experience in determining the cost of a product and setting its selling price. Furthermore, this system may help educators in delivering lectures to their students in a creative method. Students will be guided on how to use the system while absorbing the knowledge of job and batch costing simultaneously, capture their interests and turns the learning process into a more engaging and enjoyable journey.